"CAROTID": From the Greek "Karoun"—"to stupefy." Still does. Issue 3 (2nd March 2022) - Inci, Errol; Block, Peter C.
Key Points: Particularly in an elderly population, carotid artery stenting may be a suitable alternative to carotid endarterectomy with an experienced operator and careful patient selection Large randomized clinical trials comparing carotid artery stenting and carotid endarterectomy are still pending Recent update of guidelines from the European Stroke Organization is helpful for deciding which patients are best suited for carotid intervention